Posted by
**adam** on
.

how would this equation look:

y=f(x+3)

when y=f(x)= x^2

would it look like so....

x^2(x+3)

adam, there's a slight problem with your notation in the expression y = f(x+3). Ordinarily we wouldn't put an expression in place of a variable, unless we were making what is termed a composite function. I'm not sure if this is what you meant. Your second expression, y=f(x)=x^2, is a valid expression for a second degree equation. Your last expression is not correct for this function.

Let me make a guess at what the question is asking: Does it state that if you are given y=f(x)=x^2 , what is the value for f(x) when x=3?

If that is the question, then they want to know what y is when you substitute 3 for x. The response would be when x=3, y=f(3) and you would use the equation for f(x), which is x^2, to find y. If this isn't the question, write back.

No. If f(x)=x^2

then f(x+3)=(x+3)^2

the composite of F(x+3) on f(x) is (x+3)^2

Ok, then you are doing a composite function. You have f = x^2 and g = x+3 as functions of x and you want f o g.

Then f(g(x)) = (x+3)^2 as you have.

I wasn't sure in the first post what you were asking for.

When I am subtract or adding, multiplying or dividing number how do i know if it is positive or negative

-4(2x - 3) = -8x + 5

Tammy, the solution to this is simplify it.

-4(2x - 3) = -8x + 5

-8x + 12 = -8x + 5 add 8x to both sides..

12=5

which is impossible, so the original statement of

-4(2x - 3) = -8x + 5

is not possible.